If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = 45 + 12x Solving x = 45 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. x + -12x = 45 + 12x + -12x Combine like terms: x + -12x = -11x -11x = 45 + 12x + -12x Combine like terms: 12x + -12x = 0 -11x = 45 + 0 -11x = 45 Divide each side by '-11'. x = -4.090909091 Simplifying x = -4.090909091
| (2a+3)(3a-4)= | | 9=4+5x | | 75-x=x+5 | | 0.25+2x=360 | | 5y+9-y=26 | | 0.9(7x+4)=0.7-(x-3) | | 10t-6-t=9t-6 | | -10+10+-5B*2+-1+-5B= | | 4x-2+x=-2+2 | | 3(3x-8)=4x-6 | | 51x+18-29x=131 | | 8a-(1+5a)=4(3a-11)-24 | | 11b+4=37 | | 11x+8+17x-17=13x+79 | | m=m(c)2 | | 3m-1-6=13+7m | | w+2=-43-8t | | 28b^2-80b-12= | | 4x+35-15=9x-45 | | 3n+8=57 | | 1.8x+1.2x-5.4=-10 | | 2w(4w-1)=w(1-4w) | | 3(2x-1)=9x+3 | | 1a=-5a | | 0.08(x-100)=83.5-0.07 | | 3n+4=57 | | 5y+10-y=29 | | f(x)=x^2-4x-44 | | -8(v+7)+8=-33-5v | | Y+5-9=10 | | 2=2.27-4 | | 2*(5-3)-3x=5 |